Diagnostic Utility of Squash Smear Cytology in Chordoma: A Tertiary Care Center Experience - Anshima Singh; Ram Nawal Rao (Journal of Cytology)
Background and Aims: Chordomas are rare notochordal tumors. They are suitable candidates for squash smear cytology (SSC) owing to their gelatinous consistency and destructive nature. SSC is an important tool for making a quick intra-operative preliminary diagnosis and taking real-time surgical and further management decisions. This study aimed to evaluate the diagnostic accuracy of SSC for chordoma cases. Materials and Methods: This retrospective study conducted in a North Indian tertiary care center enrolled chordoma cases histopathologically diagnosed between 01.01.2013 and 31.07.2023, for which SSC was also performed. SSC smears and their corresponding histopathology slides (±immunohistochemistry [IHC] slides) were retrieved. Histo-cytological correlation was performed. Results: In total, 13 such cases were retrieved. The mean age was 34.4 + 5.6 years. The male–female ratio was 1:1.6. The most common location was the spheno-occipital region (10 cases), followed by sacro-coccygeal (two cases) and vertebral regions (1 case). The SSC was positive for chordoma in 10/13 cases. Thus, the calculated accuracy of SSC in chordoma diagnosis was 76.9%. A total of 3/13 (23.1%) cases where SSC was inconclusive for chordoma were difficult to diagnose cases, requiring IHC for ultimate diagnosis. Cytological features such as abundant myxoid matrix and physaliphorous cells help in correct diagnosis of chordoma on SSC. Conclusions: We found the diagnostic accuracy of SSC in chordoma diagnosis to be 76.9%. Features such as abundant myxoid matrix and physaliphorous cells are helpful in correct diagnosis on SSC. Thus, even though chordomas are rare, one should consider them among the differential diagnoses in cases presenting with appropriate clinico-radiological features and characteristic cytological findings.